STRATEGI DIVERSIFIKASI SUMBER PENDAPATAN MASYARAKAT DESA WISATA DI SEKITAR KAWASAN PARIWISATA NUSA DUA - Fitria Asri Satria Dewi; Yoviniani Yevri Yanseni; I Made Sujana; Fahmi Tanjung (Nusantara Hasana Journal, 2023)
The development of the Nusa Dua tourism area in Badung Regency has had a significant economic impact on the surrounding tourist village communities. However, the community's dependence on the tourism sector creates economic vulnerability when there is a decline in tourist visits. This study aims to analyze strategies for diversifying income sources for the tourist village communities around the Nusa Dua Tourism Area. The method used is a qualitative descriptive approach through observation, interviews, and documentation studies. The results show that diversification is carried out through the development of local culture-based MSMEs, traditional culinary businesses, handicrafts, tourist transportation services, integrated agriculture, and the use of digital technology in product marketing. This strategy has been proven to increase the community's economic resilience and reduce dependence on a single business sector